1992
DOI: 10.1126/science.1636091
|View full text |Cite
|
Sign up to set email alerts
|

Planar Induction of Anteroposterior Pattern in the Developing Central Nervous System of Xenopus laevis

Abstract: It has long been thought that anteroposterior (A-P) pattern in the vertebrate central nervous system is induced in the embryo's dorsal ectoderm exclusively by signals passing vertically from underlying, patterned dorsal mesoderm. Explants from early gastrulae of the frog Xenopus laevis were prepared in which vertical contact between dorsal ectoderm and mesoderm was prevented but planar contact was maintained. In these, four position-specific neural markers (engrailed-2, Krox-20, XlHbox 1, and XlHbox 6) were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(59 citation statements)
references
References 36 publications
2
56
0
1
Order By: Relevance
“…Stewart and Gerhart (1990) found that the width of the region in the late blastula that induces dorsal structures does not exceed 60". We noted above that Keller et al (199213) and Doniach et al (1992) found that planar signaling from the dorsal lip induces convergence extension and patterning in the neural plate. Our hypothesis is that even earlier planar signaling, from the vegetal cells at pregastrula stages, has a role in setting the boundaries of the neural plate.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Stewart and Gerhart (1990) found that the width of the region in the late blastula that induces dorsal structures does not exceed 60". We noted above that Keller et al (199213) and Doniach et al (1992) found that planar signaling from the dorsal lip induces convergence extension and patterning in the neural plate. Our hypothesis is that even earlier planar signaling, from the vegetal cells at pregastrula stages, has a role in setting the boundaries of the neural plate.…”
Section: Introductionmentioning
confidence: 77%
“…Keller et al (199213) used "Keller" explants of Xenopus dorsal lip and adjacent ectoderm in which only planar induction can occur to show that planar induction from the dorsal lip up to stage 11 is sufficient to induce the convergence-extension movements of the neural plate. Doniach et al (1992) used similar explants and found that several position-specific neural marker genes were expressed in the ectoderm, suggesting that planar signals are sufficient to induce a patterned neural response. These examples confirm Spemann's idea that both methods of signaling do occur and are effective, and indeed suggest that planar signaling may be the more important.…”
Section: Introductionmentioning
confidence: 99%
“…36; Developmental Biology Hybridoma Bank) were also used. For detection of Hox-B9 and En, recombinants were harvested at stage 30 for whole mount immunohistochemistry as described by Doniach et al (37). These recombinants were sectioned after staining.…”
Section: Methodsmentioning
confidence: 99%
“…Organizer-derived posteriorizing signals reach neuroectoderm during gastrulation to specify the anteroposterior axis (Nieuwkoop 1952;Doniach et al 1992;Holowacz and Sokol 1999). Besides Wnt signaling, this process requires additional pathways, such as BMP and FGF signaling.…”
Section: Cross Talk With Other Pathwaysmentioning
confidence: 99%